Conflict mobilization communities in social media as a soft power tool: problematization environmental risks - Rebrina Larisa (E3S Web of Conferences, 2021)
The object of the study is the protest communication practices of conflict mobilization in 2012-2021 by environmental communities in Russian-language social networks. Civil society is a significant actor in environmental policy. Social media as a soft power tool plays an important role today in informing, educating society about the environment and shaping a protesting regional environmental agenda. The system-communicative approach explores the patterns of discursive problematisation of environmental risks within the framework of civic political participation. Authors describe the types of publications constituting the content of environmental mobilization communities; analyse thematic dominants to identify frequent environmental threats constructed by the addressants of the publications; identify and systematise the strategies, tactics and relevant language tools used to problematise fragments of environmental reality; examine regular means of creating and maintaining online solidarity in environmental communities of conflict mobilization.